First Record of Streaked Rabbitfish Siganus Javus (L., 1766) from the Iraqi Marine Waters, with Re Description of White-Spotted Rabbitfish Siganus Canaliculatus (Park, 1797) - Al-Faisal, Abbas J.; Al-Shamary, Ahmed CH.; Yousif, Usamah H.; Younis, Kadhim H. (Iraqi Journal of Science, 2019)
Two Siganid fishes were described in the current study, the first one is Siganus javus (Linnaeus, 1766) as a new record and the other Siganus canaliculatus (Park, 1797), which was collected from the Iraqi marine waters. The samples were collected during December 2018. Streaked rabbitfish S. javus is diagnosed by a deep body, 54.01% in standard length, depth of caudal peduncle, 7.27%, total gill rakers 19 and silvery blue undulating lines on mid and lower sides of the body. Whereas the body depth of White-spotted rabbitfish S. canaliculatus was 39.08-42.66%, Caudal peduncle depth ranged from 5.21 to 5.66%, total gill rakers ranged from 22 to 24 and it is distinguished by a numerous pearly blue to whitish spots on the nape and trunk.